The Important Role of Preoperative D-Dimer in Constrictive Pericarditis - Fang L; Zhong F; Yu W; Zhu P; Yu G (Dove Medical Press, 2024)
Likui Fang, Fangming Zhong, Wenfeng Yu, Pengfei Zhu, Guocan Yu Department of Thoracic Surgery, Hangzhou Red Cross Hospital, Hangzhou, 310003, People's Republic of ChinaCorrespondence: Likui Fang, Department of Thoracic Surgery, Hangzhou Red Cross Hospital, Hangzhou, 310003, People's Republic of China, Email 21618100@zju.edu.cnBackground: The impact of coagulation indicators on postoperative outcomes of patients with constrictive pericarditis undergoing pericardiectomy has been poorly investigated. This study aimed to assess the prognostic role of preoperative coagulation indicators in these patients.Methods: We retrospectively included 158 patients with constrictive pericarditis undergoing pericardiectomy. The diagnostic values of coagulation indicators for postoperative complications were evaluated by ROC curves. Patients were divided into two groups according to the cutoff value calculated by ROC curve. Postoperative outcomes were compared between the two groups. Logistic regression analysis was performed to identify risk factors of postoperative complications.Results: ROC curve showed that among different coagulation indicators, preoperative D-dimer (DD) level could effectively identify patients with postoperative complications (AUC 0.771, 95% CI 0.696- 0.847, P < 0.001). Patients were divided into the low DD group and the high DD group. The comparison of postoperative outcomes suggested that high preoperative DD level was significantly associated with longer durations of vasoactive agents using (P = 0.018), intubation (P = 0.020), ICU stay (P = 0.008), chest drainage (P=0.004) and hospital stay (P = 0.002). Multivariable analysis showed that high preoperative DD level was the independent risk factor of postoperative complications (OR 6.892, 95% CI 2.604- 18.235, P < 0.001).Conclusion: High preoperative DD level was significantly linked to poor postoperative outcomes and could provide an effective prediction ability for postoperative complications in patients with constrictive pericarditis.Keywords: constrictive pericarditis, D-dimer, postoperative complications, outcomes